AICCRA I2G Open Innovation Challenge - Internship and Grant Opportunity: Post Sprint and Ideation Lab Report - Silwizya, Dorus (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
As part of its mission to enhance access to climate information services (CIS) and validated climate-smart agriculture (CSA) technologies in Africa, Accelerating Impact of CGIAR Climate Research for Africa (AICCRA) collaborated with BongoHive Consult on the AICCRA Internship 2 Innovation Challenge to foster the generation of cutting-edge solutions that can further enhance AICCRA's capacity, strategies, products, services, and programs. This challenge aimed to generate innovations that can be adopted and scaled to benefit farmers, students, and the country as a whole, with a particular focus on supporting small- and medium-sized Zambian agri-businesses to scale climate information services and climate-smart agriculture innovations. Through the AICCRA Zambia Accelerator Grant, AICCRA partnered with the private sector to invest in youth entrepreneurship and start-up capital, apply appropriate financial models to build climate resilience inclusively and use climate science to support Zambia's missing middle.